Harnessing the synergistic potential of coprecipitation-induced Ag3PO4 nanoparticles for environmental and biological contamination - Imran, Mohd; Eldoma, Mubarak A.; Zouli, Nasser; Hegazi, Salah Eldeen F.; Hassan, Mohamed; Parveen, Humaira; Mukhtar, Sayeed; Patil, Bhagyashree R.; Rashid, Muhammad Shahid; Ismail, Khatib Sayeed; Ali, Syed Kashif (European physical journal plus, 2025)
Silver phosphate (Ag 3 PO 4 ) , often known as silver phosphate, has recently been the subject of research due to its role in deactivating microorganisms and breaking down organic and inorganic pollutants. This is attributed to its high quantum yield. In the following study, we synthesized Ag 3 PO 4 nanoparticles (NPs) by a simple and easy coprecipitation route to study its photocatalytic and antibacterial proficiency against Alizarin Red S and various pathogens, respectively. The synthesized sample was characterized using X-ray diffractometry (XRD), energy-dispersive X-ray spectroscopy (EDX), scanning electron microscope (SEM), and X-ray photoelectron spectroscopy (XPS) analysis. The photocatalytic degradation experiment shows 85% alizarin red S dye degradation by using 5 mg catalyst. The pH 7 was found to be optimal for photodegradation as compared to acidic or alkaline pH. The concentration and time graph showed that the degradation rate also increased with the increase of time. Furthermore, various bacterial and fungal pathogens were used to evaluate the antimicrobial and antifungal activities of Ag 3 PO 4 . The findings demonstrated the broad-spectrum antibacterial activity of Ag₃PO₄. Minimum inhibitory concentration (MIC) confirms that increasing nanoparticle (NP) concentration improved pathogen inhibition. The results also showed that the lowest fungal inhibition concentration for Candida albicans fungus was 14 mm, whereas the highest bacterial inhibition concentration against Methicillin-resistant Staphylococcus aureus was 25 mm. Graphical Abstract